Choosing the right journal for your systematic review - Betini, Marluci [UNESP]; Volpato, Enilze S. N. [UNESP]; Anastacio, Guilherme D. J. [UNESP]; Faria, Renata T. B. G. de [UNESP]; El Dib, Regina [UNESP] (Wiley-Blackwell, 2014)
Rationale, aims and objectives The importance of systematic reviews (SRs) as an aid to decision making in health care has led to an increasing interest in the development of this type of study. When selecting a target journal for publication, authors generally seek out higher impact factor journals. This study aimed to determine the percentage of scientific medical journals that publish SRs according to their impact factors (>2.63) and to determine whether those journals require tools that aim to improve SR reporting and meta-analyses.Methods In our cross-sectional study showing how to choose the right journal for a SR, we selected and analysed scientific journals available in a digital library with a minimum Institute for Scientific Information impact factor of 2.63.Results We analysed 622 scientific journals, 435 (69.94%) of which publish SRs. Of those 435 journals, 135 (21.60%) provide instructions for authors that mention SRs. Three hundred journals (48.34%) do not discuss criteria for article acceptance in the instructions for authors section, but do publish SRs. Only 118 (27.00%) scientific journals require items to be reported in accordance with the specific SR reporting forms.Conclusions The majority of the journals do not mention the acceptance of SRs in the instructions for authors section. Only a few journals require that SRs meet specific reporting guidelines, making interpretation of their findings across studies challenging. There is no correlation between the impact factor of the journal and its acceptance of SRs for publication.
Keywords: Editorial policies; Journal impact factor; Medical manuscripts; Periodicals as topic; Systematic review